Foetal wastage in Cattle and Sheep at Pankshin Slaughter Slab, Plateau State, Nigeria (January–July 2024) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Foetal wastage due to the slaughter of pregnant livestock is unethical and results in economic loss. This study assessed the incidence of foetal wastage among cattle and sheep slaughtered at the Pankshin slaughter slab, Plateau State, from January to July 2024. A total of 155 cattle and 1,139 sheep were slaughtered. From these number, 77(49.7%) and 777(68.2%) were males and 78(50.3%) and 362 (31.8%) were females. Of the 78 and 362 females slaughtered, 13(8.4%) and 141(12.4%) were pregnant respectively. The investigation also shows that most cattle were slaughtered in the month of April with 27(17.4%) while majority of sheep were slaughtered in January with 226(19.8%). The rate of foetal wastage recorded in this study could be due to lack of ante-mortem inspection and poor veterinary checks. Slaughtering of animals for meat purposes should also be checked to avoid foetal wastage, which is unethical and is contrary to the international Standard Rules of slaughter. It is recommended that pregnancy examination should be carried out by experts such as veterinarians before slaughtering. Therefore complete enforcement of animal legislation should be put in place to avoid foetal wastage in livestock.